Contemporary Issues in Management: A Critical Management Approach - Lindsay Hamilton; Laura Mitchell; Anita Mangan (UK Edward Elgar, 2019)
Revised and extended for its second edition, Contemporary Issues in Management provides a unique up-to-date view of the 'messy reality' of the complex management dilemmas facing workers and managers in the business environment today. Using a critical approach, the authors offer original perspectives on organisational behaviour and the sociology of work. Presenting business case studies and analysis, this textbook covers a broad range of key themes, including ethical and social issues, diversity, migration, continuity and change. Chapters present research studies into diverse areas, from teleworking to apprenticeships, food production, volunteering and factory working. This fully updated second edition textbook provides: Discussions of management issues in their wider philosophical and political contexts to allow students to have a broader understanding and interpretation of how management affects complex real-life situations Original and in-depth qualitative case studies present lived experience rather than abstract 'model' or 'idealised' problems for successful application of theory Examples of a wide range of management practices gives students the necessary knowledge for a globalised perspective on work and business A critical approach to the topic, to develop students' analytical skills to recognise problems, and suggest suitable solutions Questions and further reading sections for use in teaching and self study. This textbook is an invaluable guide for those studying organisational behaviour and business management, as well as the sociology and ethnography of work and workplaces. Contributors include: S.B. Emery, S. French, L. Hamilton, M. Keleman, D. Knights, A. Mangan, D. McCabe, L. Mitchell, T. Oultram, G. Pearson, U. Salmon, L. Stringer, E. Surman, N. Taylor
Keywords: Management; Textbooks; (BIN3038-N) Contemporary Issues in Business Management